2011
DOI: 10.1111/j.1365-313x.2011.04570.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral expression patterns and evolutionary diversification of YABBY genes in angiosperms

Abstract: SUMMARYLateral organ growth in seed plants is controlled in part by members of the YABBY (YAB) and class III homeodomain/leucine zipper (HD-ZIPIII) families of transcription factors. HD-ZIPIII genes appear to play a conserved role in such organs, but YAB genes have diversified, with some members of the family having specialized functions in leaves, carpels or ovule integuments. The ancestral expression patterns and timing of divergence of the various classes of YAB genes remain to be established. We isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
125
3
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 64 publications
(104 reference statements)
7
125
3
7
Order By: Relevance
“…Previous studies in Arabidopsis revealed that members of the YABBY gene family act redundantly to regulate complex patterning and growth decisions in lateral organ development (Bowman and Smyth 1999;Eshed et al 1999;Sawa et al 1999;Siegfried et al 1999;Villanueva et al 1999;Bowman 2000;Sarojam et al 2010;Finet et al 2016 (Yamada et al 2011). FIL and YAB3 act together to promote leaf growth and expansion, including some aspects of adaxialabaxial polarity (Siegfried et al 1999).…”
Section: Yabby Gene Function and Ear Internode Lengthmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in Arabidopsis revealed that members of the YABBY gene family act redundantly to regulate complex patterning and growth decisions in lateral organ development (Bowman and Smyth 1999;Eshed et al 1999;Sawa et al 1999;Siegfried et al 1999;Villanueva et al 1999;Bowman 2000;Sarojam et al 2010;Finet et al 2016 (Yamada et al 2011). FIL and YAB3 act together to promote leaf growth and expansion, including some aspects of adaxialabaxial polarity (Siegfried et al 1999).…”
Section: Yabby Gene Function and Ear Internode Lengthmentioning
confidence: 99%
“…The YABBY gene family consists of five clades, namely CRABS CLAW (CRC), INNER NO OUTER (INO), YABBY3/FILAMENTOUS FLOWER (YAB3/FIL), YABBY2 (YAB2), and YABBY5 (YAB5) (Yamada et al 2011). FIL and YAB3 act together to promote leaf growth and expansion, including some aspects of adaxialabaxial polarity (Siegfried et al 1999).…”
Section: Yabby Gene Function and Ear Internode Lengthmentioning
confidence: 99%
See 3 more Smart Citations